Upper and Lower Limb Motor Function Correlates with Ipsilesional Corticospinal Tract and Red Nucleus Structural Integrity in Chronic Stroke: A Cross-Sectional, ROI-Based MRI Study - Denise M. Peters; Julius Fridriksson; Jessica D. Richardson; Jill C. Stewart; Chris Rorden; Leonardo Bonilha; Addie Middleton; Stacy L. Fritz (Behavioural Neurology)
Background. Structural integrity of the ipsilesional corticospinal tract (CST) is important for upper limb motor recovery after stroke. However, additional neuromechanisms associated with motor function poststroke are less well understood, especially regarding the lower limb. Objective. To investigate the neural basis of upper/lower limb motor deficits poststroke by correlating measures of motor function with diffusion tensor imaging-derived indices of white matter integrity (fractional anisotropy (FA), mean diffusivity (MD)) in primary and secondary motor tracts/structures. Methods. Forty-three individuals with chronic stroke (time poststroke, 64.4±58.8 months) underwent a comprehensive motor assessment and MRI scanning. Correlation and multiple regression analyses were performed to examine relationships between FA/MD in a priori motor tracts/structures and motor function. Results. FA in the ipsilesional CST and red nucleus (RN) was positively correlated with motor function of both the affected upper and lower limb (r=0.36‐0.55, p≤0.01), while only ipsilesional RN FA was associated with gait speed (r=0.50). Ipsilesional CST FA explained 37.3% of the variance in grip strength (p<0.001) and 31.5% of the variance in Arm Motricity Index (p=0.004). Measures of MD were not predictors of motor performance. Conclusions. Microstructural integrity of the ipsilesional CST is associated with both upper and lower limb motor function poststroke, but appears less important for gait speed. Integrity of the ipsilesional RN was also associated with motor performance, suggesting increased contributions from secondary motor areas may play a role in supporting chronic motor function and could become a target for interventions.